A Review Essay on Handbook of Industrial Organization - Porter, Robert H. (Journal of Economic Literature, 1991)
THIS ARTICLE critically reviews the Handbook of Industrial Organization (henceforward the Handbook), edited by Richard Schmalensee and Robert Willig. These two volumes are the tenth installment in the North-Holland Handbooks in Economics series, under the general editorship of Kenneth Arrow and Michael Intriligator. Like its predecessors, this Handbook contains a number of survey papers (in this instance, 26) on a variety of related topics. As such, they afford both authors and readers an opportunity to determine which directions research in the field has taken, what (if any) real advances have been made, and what questions are still unanswered. Consequently, this review also describes and appraises the current state of Industrial Organization. Research in Industrial Organization has undergone a dramatic change in the last 20 years. Neoclassical decision-theoretic analysis and competitive general equilibrium theory have been supplanted almost completely by noncooperative game theory. This change was not merely the adoption of the tools of another field.